Iklim Keselamatan Kerja dan Big Five Personality Sebagai Prediktor Perilaku Keselamatan Karyawan - Puspa Prabarini; Fendy Suhariadi (Jurnal Psikologi Teori dan Terapan, 2018)
Stevedoring activities at container terminals make it one of the most dangerous workplace for employees because they have to deal with variety of high-risk conditions as well as high-risk equipments. Therefore it is not suprising that container terminals have high occupational accidents rate. Furthermore, several statistical reports also indicate that most maritime accidents are attributable to human error. The purpose of this study is to explain the effect of safety climate and big-five personality on employee safety performance. Safety climate and big five personality are considered as two factors that influence employee safety performance. Therefore strong positive safety climate in organization will be able improve employee safety performance and reduce accidents. This study was conducted to 148 employees in a container terminal by using simple random sampling as the sampling technique. Multiple regression technique was used to examine the effect of safety climate and big-five personality on employee safety performance. The result revealed that safety climate and big-five personality positively affect employee safety performance.Key words: Safety climate, big five personality, safety performanceAbstrak: Aktivitas bongkar muat pada terminal peti kemas menjadikannya sebagai salah satu tempat kerja yang paling berbahaya karena karyawan harus menghadapi beragam aktivitas yang beresiko tinggi dan peralatan kerja yang berbahaya.  Maka dari itu, bukan suatu hal yang mengejutkan bahwa terminal peti kemas memiliki tingkat kecelakaan kerja yang tinggi. Lebih jauh lagi, sejumlah data statistik juga menunjukkan bahwa mayoritas kecelakaan kerja pada sektor industri maritim berkaitan dengan kesalahan manusia. Tujuan dari penelitian ini adalah untuk menjelaskan pengaruh iklim keselamatan kerja dan big five personality terhadap perilaku keselamatan karyawan. Penelitian ini dilakukan pada 148 karyawan di salah satu terminal peti kemas dengan menggunakan simple random sampling sebagai teknik sampling. Analisis regresi berganda digunakan untuk menguji pengaruh antara iklim keselamatan kerja dan big five personality terhadap perilaku keselamatan karyawan. Hasil studi menunjukkan bahwa iklim keselamatan kerja dan big five personality secara positif berpengaruh pada perilaku keselamatan karyawan.